Strength Based Group Counseling untuk Meningkatkan Academic Hardiness Siswa - Ramadhoni, Sri Rahmah; Azizah, Nurul; Wibowo, Mungin Eddy; Purwanto, Edy (Jurusan Bimbingan dan Konseling Islam, 2019)
The purpose of this research is to determine the effectiveness of Strength based group counseling to increase academic hardiness of students. The research method is an experiment using the design of one group pre-test and post-test by involving 7 students of SMAN 5 Kota Semarang who had low academic hardiness. The data collection used was academic hardiness scale. The results of this research indicate the students' academic hardiness before being given Strength based group counseling, average academic hardiness of 32,71 (SD = 1.380), then increased after Strength based group counseling was 51,29 (SD =1.799). Paired sample t-test results showed that Strength based group counseling was effective to increase academic hardiness of senior high school students (t =-19,598 p < 0.01). This research confirms that Strength based group counseling can be applied to increase academic hardiness of students and asserts that Strength based group counseling has an implication toward the optimization of counselors’ roles and professionalism in the utilization of Strength based group counseling for the development of positive behaviors.